Five Husbands' Negligence in Fulfilling Their Child Maintenance Obligations after Divorce: A Phenomenological Study in a Muslim Community - Purnanda, Defri; Burhanuddin, Burhanuddin; Hamdi, Isnadul; Daharis, Ade (Jurnal Elsyakhshi, 2024)
One of the phenomena that often occurs after the divorce of a husband and wife is related to the fulfillment of child support by the husband. Typically, the husband is still obligated to provide child support to ensure that the child’s rights are properly met. However, in Muslim communities, there are still cases where husbands do not fulfill this responsibility, creating a polemic for the children and wives left behind. Therefore, this study aims to explore the phenomenon within Muslim communities related to the issue of a husband's responsibility for child support after divorce. This research uses qualitative methods with a phenomenological approach. Data were collected through individual interviews with fourteen informants, consisting of three husbands, six wives, and five family members. All informants were selected using a snowball sampling technique, and data were analyzed using the Miles & Huberman technique. Overall, the research findings reveal five types of negligence by husbands regarding child maintenance after divorce. The types of negligence include: i) the husband remarries and subsequently neglects his responsibility to provide for the child, ii) loss of communication with the family due to relocation, iii) financial instability, iv) lack of commitment to fatherly responsibilities, and v) shifting the full burden of child maintenance to the wife. These findings serve as a lesson and a strong moral message for Muslim communities, especially for divorced husbands, about the importance of responsibility and commitment in fulfilling child support obligations after divorce.